2009
DOI: 10.1111/j.1468-3083.2009.03267.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of CRTH2 on eosinophils in allergic skin diseases

Abstract: The Student's t-test was used to assess the statistical significance of differences between mean values of healthy subjects and patients. *P < 0.05.Abbreviations: CRTH2, chemoattractant receptor-homologous molecule expressed on Th2 cells; PGD2 prostaglandin D2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Our prior study suggested that there was a possible involvement of the PGD2-CRTH2 interaction in these diseases. 45 Most notably, the skin lesions found in these diseases are histologically characterized by a marked basophil infiltration. 46 Thus, basophil-derived PGD2 may at least partly contribute to the pathogenesis of these inflammatory skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior study suggested that there was a possible involvement of the PGD2-CRTH2 interaction in these diseases. 45 Most notably, the skin lesions found in these diseases are histologically characterized by a marked basophil infiltration. 46 Thus, basophil-derived PGD2 may at least partly contribute to the pathogenesis of these inflammatory skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…23 Expression of CRTH2 in eosinophils is increased in patients with atopic dermatitis, chronic urticaria or prurigo. 24 Antagonists of CRTH2 ameliorate skin inflammation in IgE-mediated chronic skin responses, contact hypersensitivity and cedar pollen dermatitis in accordance with reduced numbers of dermal eosinophils. 20,21,25 Recent studies have identified indomethacin as a potent agonist of CRTH2, 26 causing PGD 2 -like and eotaxin (CCL11) -like responses in eosinophils.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…29 CRTH2 expression is increased in eosinophils of atopic dermatitis, chronic urticaria, and in prurigo patients. 30 CRTH2-expressing T cells are elevated in the blood of atopic dermatitis. 31 Despite the different lines of evidence previously mentioned, the in vivo roles of DP in inflammation are somewhat controversial.…”
mentioning
confidence: 97%